Allocation risk and prior allocation behavior of health & hygiene resources in supply - side reform in China. Issue 5 (4th July 2018) - Tian, Man-Wen; Yan, Shu-Rong; Tian, Xiao-Xiao
Abstract: In view of the limited budget of governmental finance and high demands on health and hygiene resources, government needs to study the decision-making issues concerned about the prior allocation behavior of governmental hygiene resources under the circumstance of co-existing disease risk and medical treatment risk in the supply side reform of medical health field. In this paper, the risk preference conditions of social planner for co-existing disease risk and treatment risk having influence on the hygiene allocation of the higher risk group were provided. When both risks are co-existing, the preference conditions of social planner under the single risk are ineffective for him/her for allocating more hygiene resources. The joint effect of the two types of risks is uncertain; however it can be eliminated by applying new risk preference conditions. This paper focuses on researching the hygiene resource allocation sorting risk source under an uncertain condition and finding the important role of the correlation between two risks for the governmental decision on hygiene resource allocation, they will have important significance for deeply pushing the supply side reform of medical health field, improving medical health supply structure and improving public health.